ANALISIS KOMUNIKASI INTERPERSONAL ANTARA BARISTA DAN PELANGGAN DI KEDAI KOPI DAKSA RAHAYU KOTA MALANG - Felisa Zalianti Putri (Jurnal Komunikasi, 2024)
Communication is one of the most important things in supporting daily activities. This research aims to analyze interpersonal communication between baristas and customers in coffee shops. This research uses qualitative data analysis techniques. The effectiveness of interpersonal communication is influenced by various factors, including personal, situational, and cultural factors. Strategies to increase the effectiveness of interpersonal communication need to be implemented on an ongoing basis to achieve maximum customer satisfaction. This research also aims to increase customer interest in returning to subscribe because of the quality of communication. The research results show that interpersonal communication between baristas and customers has an important role in building relationships and creating positive experiences for customers. Baristas use a variety of communication techniques, such as friendliness, attentiveness, and personalization, to build relationships with customers and make them feel valued